Avaliação de impacto do projeto Escola Estadual de Tempo Integral em Goiás - Costa, Rafael dos Reis (2017)
The State School Program of Full Time, started in 2006 in the state of Goiás. It have 135 schools attended in 2013. This program offers cultural and sports activities, besides school reinforcement. The study intends to evaluate the project impacts on the academic performance in portuguese language and math of the 5th and 9th graders with data from the Brazil Proof (Prova Brasil) of 2013. To achieve this goal was used the method of propensity score matching. The results found point to non-significant effects in mathematics and portuguese language for the 5th graders. On the other hand, the 9th graders who study in schools that participated in the program before 2013 the effects are positive. Those in schools that started the program in 2013 did not have a significant difference in math, but did a negative and significant performance in comparison with the control group in portuguese language.